Overcoming the lack of authentic standards for the quantification of biogenic secondary organic aerosol markers. Issue 1 (14th December 2022) - Bryant, Daniel J.; Mayhew, Alfred W.; Pereira, Kelly L.; Budisulistiorini, Sri Hapsari; Prior, Connor; Unsworth, William; Topping, David O.; Rickard, Andrew R.; Hamilton, Jacqueline F.
Abstract : Liquid chromatography coupled to electrospray ionisation high resolution mass spectrometry is an extremely powerful technique for both targeted and non-targeted analysis of organic aerosol. Abstract : Liquid chromatography coupled to electrospray ionisation high resolution mass spectrometry is an extremely powerful technique for both targeted and non-targeted analysis of organic aerosol. However, quantification of biogenic secondary organic aerosol species (BSOA) is hindered by a lack of commercially available authentic standards. To overcome the lack of authentic standards, this study proposes a quantification method based on the prediction of relative ionisation efficiency (RIE) factors to correct concentrations obtained via calibration using a proxy standard. RIE measurements of 89 commercially available standards were made relative to cis -pinonic acid and coupled to structural descriptors. A regularised random forest predictive model was developed using the authentic standards ( R 2 = 0.66, RMSE = 0.59). The model was then used to predict the RIE's of 87 biogenic organic acid markers from α-pinene, limonene and β-caryophyllene without available authentic standards. The predicted RIE's ranged from 0.27 to 13.5, with a mean ± standard deviation of 4.2 ± 3.9. 25 markers were structurally identified in chamber samples and ambient aerosol filter samples collected in summertime Beijing. The markers were quantified using a cis -pinonic acid calibration and then corrected using the predicted RIE factors. This resulted in the average BSOA concentration decreasing from 146 ng m −3 to 51 ng m −3, respectively. This change in concentration is highlighted to have an impact on the types of average aerosol metrics commonly used to describe bulk composition. This study is the first of its kind to use predicted ionisation efficiency factors to overcome known differences in BSOA concentrations due to the inherent lack of authentic standards in aerosol chemistry.